2017
DOI: 10.1016/j.jvs.2016.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Pilot assessment of a human extracellular matrix-based vascular graft in a rabbit model

Abstract: Background Herein we describe a small-diameter vascular graft constructed from rolled human amniotic membrane (hAM), with in vitro evaluation and subsequent in vivo assessment of its mechanical and initial biological viability in the early post-implantation period. This approach for graft construction allows for customization of graft dimensions, with wide-ranging potential clinical applicability as a non-autologous, allogeneic, cell-free graft material. Methods and Results Acellular hAM were rolled into lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…0.2 M trehalose +10% v/v DMSO Freezing with 1 K/min to −50 C freezedried for 7 hr at −50 C. Stored in vacuum at room temperature 1 v/v DMSO Fresh cell culture medium acted as a control provides safe and effective treatment to achieve pain control in patients with NCP.Along with its effectiveness in ophthalmology, hAM grafts have been employed in the cardiovascular field. Amensag et al57 constructed a small-diameter (3.2 mm diameter) vascular graft from rolled human amniotic membrane and evaluated mechanical properties and viability in vivo in a rabbit model in the early postimplantation period. After 4 weeks, the constructed graft showed evidence of active cellular remodeling and did not present hyperacute rejection or thrombotic occlusion.…”
mentioning
confidence: 99%
“…0.2 M trehalose +10% v/v DMSO Freezing with 1 K/min to −50 C freezedried for 7 hr at −50 C. Stored in vacuum at room temperature 1 v/v DMSO Fresh cell culture medium acted as a control provides safe and effective treatment to achieve pain control in patients with NCP.Along with its effectiveness in ophthalmology, hAM grafts have been employed in the cardiovascular field. Amensag et al57 constructed a small-diameter (3.2 mm diameter) vascular graft from rolled human amniotic membrane and evaluated mechanical properties and viability in vivo in a rabbit model in the early postimplantation period. After 4 weeks, the constructed graft showed evidence of active cellular remodeling and did not present hyperacute rejection or thrombotic occlusion.…”
mentioning
confidence: 99%
“…99 Amensag et al used decellularized hAM and thrombin glue to form a six-layered graft that supported the culture of SMCs, which ultimately increased the elastic modulus and GAG content, but decreased the physiological modulus. 100 All three acellular grafts displayed significant remodeling and remained patent after 4 weeks in New Zealand white rabbits, although there was thrombus formation in one graft. 100 Alternatively, bovine pericardium, a nonthrombogenic source of ECM, 101 is frequently used clinically as a vascular patch, 102 but it has only recently been employed for small-diameter vascular grafts.…”
Section: Two-dimensional Tissuementioning
confidence: 90%
“…100 All three acellular grafts displayed significant remodeling and remained patent after 4 weeks in New Zealand white rabbits, although there was thrombus formation in one graft. 100 Alternatively, bovine pericardium, a nonthrombogenic source of ECM, 101 is frequently used clinically as a vascular patch, 102 but it has only recently been employed for small-diameter vascular grafts. 103 Vascular grafts composed of decellularized bovine pericardium, coupled with poly(propylene fumarate), demonstrated a modulus similar to native vessels, with ample burst pressure and suture retention strength to support physiological pressures.…”
Section: Two-dimensional Tissuementioning
confidence: 90%
“…The luminal surface of the graft showed endothelial cell coverage and cellular infiltration of the medial layer [ 10 ]. In vivo performance of decellularized xenogenic non-arterial tissues, such as bovine ureter or human amniotic membrane, were also evaluated in animal models [ 12 , 122 ]. But in a human hemodialysis access trial, Chemla et al found that a decellularized bovine ureter (SG100) did not have an advantage in graft patency or stability over expanded polytetrafluoroethylene (ePTFE) [ 5 ].…”
Section: In Vivo Performance Of Decellularized Vascular Graftsmentioning
confidence: 99%